Spermine and L-name pretreatment effects on polyamine and nitric oxide metabolism in rat brain during seizures - Stojanović Ivana; Jelenković Ankica; Vasiljević Ivana; Pavlović Dušica; Bjelaković Gordana (Journal of Medical Biochemistry, 2007)
In the CNS polyamines can exert opposite effects, depending on the concentration and conditions in the cell. Protective or neurotoxic polyamine effects were documented during seizures and repeated CNS excitation. Intensive research of exogenous polyamines effects during seizures induced by numerous agents did not clear up confusions about the duality of effects and the role of polyamines in seizures. In order to understand polyamine modulatory effects in seizures, the importance of NO and polyamine metabolism interdependence and the possible implication of changes of postulated NO and polyamine equillibrium in seizures, the effects of spermine alone and in combination with L-NAME (NOS inhibitor) on seizures induced by pentazol (PTZ) were investigated. To compare the obtained results, the effects of anticonvulsant midazolam on NO production during seizures were also investigated. Seizures were induced by i.p. application of pentazol (100 mg/kg b.w). Spermine and L-NAME were administered i.p. before PTZ. In the striatum and hippocampus, spermine induced increased NO production (p<0.001) related to values in the group treated by PTZ. Application of L-NAME before spermine and PTZ caused decrease of NO production in comparison with animals treated only by PTZ or spermine and PTZ. L-NAME given before spermine exerts protective effects related to seizures induced by PTZ and to the group treated by spermine, extending the time of seizure symptoms appearance, thus confirming the NO signaling system involvement in spermine effects during seizures. Highly significant PAO activity increase caused by spermine points out the intensified interconversion of spermine into putrescine, in order to maintain the intracellular putrescine concentration. The obtained results prove a strong relationship between the NO signaling system and polyamine metabolism in the brain during seizures and the importance of their changes in this kind of CNS injury.